Evaluating the economic screening of cervical cancer using IVA, HPV DNA, and histology methods: Systematic review - Rofika, Ana; Ratnasari , Desi; Christiana , Indah; Siti Fatimah, Okta Zenita; ST. Mukarromah; Mufdillah; Listiani , Putri (Journal of Health Technology Assessment in Midwifery, 2023)
Background: Cervical cancer is a common malignancy causing cancer-related deaths worldwide. Evidence suggests that adequate screening can reduce cervical cancer-related deaths. Screening for cervical cancer can be done using Visual Inspection of Acetic Acid (VIA), HPV DNA and cytology. The economic burden of cancer patients is substantial ranging from US$8,066 to 22,888 per patient. Health cost effectiveness was comparative in the analysis of costs and consequences for the three screening methods. VIA is the most cost-effective primary screening test for cervical cancer. Purpose: To review the research results of a full economic evaluation to encourage the specific cervical cancer screening methods used to enhance the detection of precancerous lesions in women's cervix. Method: This systematic review used the PRISMA ScR framework with a literature search using 3 databases, namely Pubmed, Wiley, and Google Scholar, with years of publication from 2009 – 2023. The data that has been obtained is carried out by critical appraisal using the Consolidated Health Economic Evaluation Reporting Standards (CHEERS). Results: Based on the search for 3,973 selected articles, 7 match the inclusion criteria. This systematic review discovered three major themes: the utility value of health status, cost and analysis. Conclusion: The most cost-effective cervical cancer screening is by VIA. HPV DNA and pap smear based cytology techniques have been reported to show high sensitivity and specificity respectively including being expensive and resource intensive. In contrast the VIA technique has moderate sensitivity and specificity but is less expensive Various developed countries have used Pap or HPV DNA cytology tests as the main screening method, which can lead to a 50-70% reduction in cervical cancer incidence, while in developing countries using VIA tests as a cervical cancer screening method.